Stability of Nuclear Reactor: Point Model Analysis - Bučys, K.; Švitra, D. (Nonlinear Analysis: Modelling and Control, 2006)
A point model of a nuclear reactor with delay in feedback line “ower – reactivity” estimating the influence of six groups of delayed neutrons is presented and investigated by means of linear and nonlinear analysis methods. The results of numerical experiments and the comparison of them to the asymptotic solution of differential equations are presented as well.
Keywords: nuclear reactor; differential equation; delay; periodic solution